KORELASI LEMAK TUBUH DENGAN KEMAMPUAN LOMPAT JAUH PADA ATLET LOMPAT JAUH FIK UNM - Sulaiman Sulaiman; Sarifin G; Hasmyati Hasmyati (Jurnal Ilara : Jurnal Hasil Penelitian, Aplikasi Teori, Analisa, Dan Pembahasan Kepustakaan tentang Keolahragaan, 2022)
Based on the results of the analysis, the results of data processing can be seen that there is an correlation of body fat to the distance of the jump in long jump athletes at the FIK UNM from the regression test data for fat thickness N (sample) of 12 people, mean 5634, T table value 22,861 and sig. ) 0.00 (p <0.05). means that the fat thickness data is normally distributed. Then from the long jump regression test data N (sample) 12 people, Mean 1.7873, T table value 33.367 and sig. (2 tailed) 0.00 (p <0.05). means the long jump data is normally distributed. And it can be seen that there is a correlatiom of body fat with long jump ability in terms of fat thickness in long jump athletes FIK UNM with a difference or difference of 1.2239.